Fluidic origami cellular structure with asymmetric quasi-zero stiffness for low-frequency vibration isolation - Sadeghi, Sahand; Li, Suyi (Smart materials and structures, 2019)
This study investigates a unique asymmetric quasi-zero stiffness (QZS) property from the pressurized fluidic origami cellular structure, and examines the feasibility and efficiency of using this nonlinear property for low-frequency vibration isolation. This QZS property of fluidic origami stems from the nonlinear geometric relationships between folding and internal volume change, and it can be programmed by tailoring the constituent Miura-Ori crease design. Different fluidic origami cellular structure designs are introduced and examined to obtain a guideline for achieving QZS property. A proof-of-concept prototype is fabricated to experimentally validate the feasibility of acquiring QZS. Moreover, a comprehensive dynamic analysis is conducted based on numerical simulation and harmonic balance method approximation. The results suggest that the QZS property of fluidic origami can successfully isolate base excitation at low frequencies. In particular, this study carefully examines the effects of an inherent asymmetry in the force-displacement curve of pressurized fluidic origami. It is found that such asymmetry could significantly increase the transmissibility index with certain combinations of excitation amplitude and frequency, and it could also induce a drift response. Outcome of this research can lay the foundation for new origami-inspired multi-functional metamaterials and meta-structures with embedded dynamic functionalities. Moreover, the investigations into the asymmetry in force-displacement relationship provide valuable insights for many other QZS structures with similar properties.